The ABC of diabetes. How many patients are able to achieve the goal laid down by American Diabetes Association? - Menon, A.S. (Med J Armed Forces India, 2015)
BACKGROUND: To study the number of patients with Type 2 Diabetes Mellitus who achieve the glycemic, blood pressure and LDL-Cholesterol targets as per American Diabetes Association, Standard of Care for Management of Diabetes. METHODS: Hundred patients of Type 2 Diabetes mellitus were recruited from December 2008 to January 2009 from an Endocrinology OPD of tertiary care hospital and followed up for six months. Glycosylated hemoglobin (HbA1c), blood pressure (BP) and LDL-Cholesterol (LDL) were estimated at baseline and prevalence of those at target (HbA1c <7%, BP < 130/80 mm Hg, LDL < 100 mg/dl) was documented and repeated at three and six months to monitor improvement in the number of patients at target and trend in improvement of individual parameters. RESULTS: The percentage of patients at target at baseline and six months for HbA1c was (45% vs. 55% p = 0.101), BP < 130/80 mm Hg (27% vs. 25%) and LDL <100 mg/dl (37% vs. 40% p = 0.386). All three parameters were at target in one patient and three patients at six months period. Mean values at baseline and six months of HbA1c 7.46% (95% CI 7.17–7.75) vs 7.21% (95% CI 6.9–7.52), Systolic BP 138 mm Hg (95% CI 135–141), Diastolic BP 86 mm Hg (95% CI 84–86) and LDL 114 mg/dl (95%CI 107–121) vs. 110 mg/dl (95%CI 105–116) did not show significant improvement (p for trend). CONCLUSION: Standards of care for HbA1c, blood pressure and LDL remains to be achieved in majority of the diabetic patients.